2018
DOI: 10.31234/osf.io/tf5sc
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stability and Fluctuation of Personality Disorder Features in Daily Life

Abstract: Very little is known about the daily stability and fluctuation of personality pathology. To address this gap in knowledge, we investigated the naturalistic manifestation of personality pathology over the course of 100 days. A group of individuals (N=101) diagnosed with any personality disorder (PD) completed a daily diary study over 100 consecutive days (Mdn = 94 days, Range = 33-101 days). Participants completed daily ratings of 30 manifestations of personality pathology. Patterns of stability and variabi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 41 publications
2
52
0
Order By: Relevance
“…Sample 3. Participants from sample 3 were taken from an ecological momentary assessment study of individuals with clinically diagnosed personality disorders (23,24). Participants (n = 101) completed ratings of psychosocial and interpersonal experiences once per day for 100 d. Complete details regarding recruitment, diagnosis, and study procedures can be found in the studies by Wright et al (23) and Wright and Simms (24).…”
Section: Methodsmentioning
confidence: 99%
“…Sample 3. Participants from sample 3 were taken from an ecological momentary assessment study of individuals with clinically diagnosed personality disorders (23,24). Participants (n = 101) completed ratings of psychosocial and interpersonal experiences once per day for 100 d. Complete details regarding recruitment, diagnosis, and study procedures can be found in the studies by Wright et al (23) and Wright and Simms (24).…”
Section: Methodsmentioning
confidence: 99%
“…Daily expression of PD was measured using 30 items created for this project. Details related to full item set and scale development can be found in Wright and Simms (2016) MANOVA. We conducted a one-way multivariate analysis of variance (MANOVA) to evaluate if the average level of symptoms across the days used in the present study differed across the subgroups obtained from S-GIMME.…”
Section: Empirical Studymentioning
confidence: 99%
“…Referred to variously as experience sampling, ecological momentary assessment, or ambulatory assessment (Shiffman, Stone, & Hufford, 2008;Trull & Ebner-Primer, 2013), these approaches generally use intensive longitudinal data collection designs to sample behavior on a time-scale closer to the dynamic processes they intend to measure. Research in psychopathology increasingly relies on these methods to understand the nuanced and complex dynamic processes of mental illness (e.g., Ebner-Priemer et al, 2007;Hamaker & Wichers, 2017;Muehlenkamp et al, 2009;Myin-Germeys, van Os, Schwartz, Stone, & Delespaul, 2001;Pe et al, 2015;Sadikaj et al, 2013;Shiffman et al, 2002;Silk, Steinberg, & Morris, 2003;Smyth et al, 2007;Trull et al, 2008;Wright & Simms, 2016; see also Myin-Germeys et al, 2009 andEbner-Priemer, 2013 for reviews). This work has almost exclusively relied on the aforementioned diagnostic classification schemes by placing individuals in predefined groups and conducting analysis under the assumption of within-group homogeneity.…”
mentioning
confidence: 99%
“…Careful design of these studies will allow for the identification of how threats to the ego of narcissistic individuals relate to cognitive, emotional, and behavioral outcomes. There is an emergent literature that suggests relative stability of narcissism and related traits (e.g., self‐esteem, grandiosity; Wright & Simms, ), although it may differ by narcissism dimension (Guekes et al, ), but a more granular understanding of how traits function differently by situation is lacking. We believe that the frequency, intensity, and duration of different affective and interpersonal responses to threat are a key component of understanding the overlap between narcissistic grandiosity and vulnerability.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Although the empirical profiles associated with these narcissism dimensions are largely dissimilar, this is at odds with many theoretical perspectives that emphasize the joint role of grandiosity and emotional/ego‐based vulnerability in narcissism, as well as clinical reports that suggest narcissistic clients “virtually always” display traits of both grandiosity and vulnerability (Pincus, Cain, & Wright, , p. 440) that oscillate over the course of treatment. However, very little research has attempted to address the question of whether narcissistic grandiosity and vulnerability fluctuate within individuals across time, although some research exists that demonstrates grandiosity is relatively stable over time (Giacomin & Jordan, ; Lavner, Lamkin, Miller, Campbell, & Karney, ; Wright & Simms, ).…”
Section: Introductionmentioning
confidence: 99%